Petrology and Nd–Hf Isotope Geochemistry of the Neoproterozoic Amon Kimberlite Sills, Baffin Island (Canada): Evidence for Deep Mantle Magmatic Activity Linked to Supercontinent Cycles. (24th September 2014) - Tappe, Sebastian; Kjarsgaard, Bruce A.; Kurszlaukis, Stephan; Nowell, Geoff M.; Phillips, David
Abstract: The c. 673 Ma (U–Pb rutile) Amon kimberlites located in northern Baffin Island intruded Late Archean basement rocks of the Rae craton as a subhorizontal sill complex. The Amon sills are part of widespread low-volume, volatile-rich ultramafic magmatism that occurred along the northern and eastern margins of Laurentia, demarcating the temporal and spatial breakout from the Rodinia supercontinent during the Late Neoproterozoic. Numerous other known kimberlite occurrences that are related to these rifting events between c. 680 and 540 Ma are located in mainland Nunavut, Ontario, Quebec, Labrador, and West Greenland. The magmas that fed the Amon sills are archetypal Group-I kimberlites, based on groundmass mineralogy (e.g. phlogopite, spinel, ilmenite) and bulk-rock compositions, including moderately depleted Sr–Nd–Hf isotope ratios. However, a wide compositional range, together with observed flowage textures, indicates that some magma differentiation occurred during sill emplacement. The Amon samples that are interpreted as parental kimberlite magma compositions overlap published compositions of experimentally derived, near-solidus partial melts of carbonated peridotite between 5 and 10 GPa; that is, equivalent to an origin from 150 to 300 km depth. Furthermore, the Amon kimberlites are characterized by moderately depleted Nd (εNd(i) = +1·5 to +3·5) and Hf (εHf(i) = +1·1 to +8·7) isotope compositions, without pronounced isotope decoupling as known from other kimberlite occurrences worldwide. Among the studied Late Neoproterozoic volatile-rich ultramafic magmatic rocks in Laurentia, the Amon kimberlites have Nd–Hf isotope systematics that are similar to those of a previously identified, carbonate-rich, depleted end-member component. This common component is suggested to represent a widespread near-solidus partial melt of volatile-fluxed fertile peridotite within the uppermost convecting mantle beneath the rifting supercraton. Our preferred model for Late Neoproterozoic kimberlite and related magmatism along the rifted margins of Laurentia invokes a combination of redox- and decompression-related low-degree partial melting of convecting upper mantle material that flows beneath rugged topography at the base of thick continental lithosphere. Provided that carbonate metasomatism of lower cratonic mantle is ubiquitous on a global scale, we argue that proto-kimberlitic melt is likely to be constantly present beneath the cratonic roots of supercontinents, and that it is most efficiently extracted during fast and changing plate motions, such as during the assembly and break-up of supercontinents. This idea is supported by the known kimberlite emplacement patterns of the Gondwana–Pangea (510 Ma–Recent) and Rodinia (1300–550 Ma) supercontinent cycles, but it remains difficult to test for older kimberlites and related rocks dating back to c. 3 Ga.